Dissertation: “Assembling Women. Performance and Community in the Tanagra Figurines” - Emily C. Mohr (Les Carnets de l’ACoSt)
This dissertation approaches the Tanagras from feminist and phenomenological perspectives by analyzing aspects of the figurines’ manufacture, patronage, context(s), and their connections to ancient people’s lived experiences. Supervisor: Professor Sheila Dillon.